1995
DOI: 10.1073/pnas.92.8.3308
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial activation-based molecular bioimprinting of lipolytic enzymes.

Abstract: Interfacial activation-based molecular (bio)-imprinting (IAMI) has been developed to rationally improve the performance of lipolytic enzymes in nonaqueous environments. The strategy combinedly exploits (i) the known dramatic enhancement of the protein conformational rigidity in a water-restricted milieu and (ii) the reported conformational changes associated with the activation of these enzymes at lipid-water interfaces, which basically involves an increased substrate accessibility to the active site and/or an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
84
1

Year Published

1998
1998
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 140 publications
(88 citation statements)
references
References 33 publications
(34 reference statements)
3
84
1
Order By: Relevance
“…It was suggested that the two conformers, "closed" poor active and "open" active forms, should be taken into account when we employ lipases as a biocatalyst, especially in a water-restricted environment where lack of interfacial activation is observed (Lowrier et al, 1996). In this regard, Mingarro et al reported a novel concept for the activation of lipolytic enzymes, interfacial activation-based molecular bioimprinting (IAMI), for use in nonaqueous media (Mingarro et al, 1995(Mingarro et al, , 1996. Their strategy is based on the molecular imprinting technique of other enzymes (Russell and Klibanov, 1988): the combination of the creation of the activated form of enzymes in aqueous media and the retention of the imprinted conformation in nonaqueous media.…”
Section: Introductionmentioning
confidence: 96%
“…It was suggested that the two conformers, "closed" poor active and "open" active forms, should be taken into account when we employ lipases as a biocatalyst, especially in a water-restricted environment where lack of interfacial activation is observed (Lowrier et al, 1996). In this regard, Mingarro et al reported a novel concept for the activation of lipolytic enzymes, interfacial activation-based molecular bioimprinting (IAMI), for use in nonaqueous media (Mingarro et al, 1995(Mingarro et al, , 1996. Their strategy is based on the molecular imprinting technique of other enzymes (Russell and Klibanov, 1988): the combination of the creation of the activated form of enzymes in aqueous media and the retention of the imprinted conformation in nonaqueous media.…”
Section: Introductionmentioning
confidence: 96%
“…A similar effect may occur with the presence of hydrophobic alkyl groups in the gel. Lipophilic interactions between the hydrophobic parts of the gel and lipase during the sol-gel process can fix the encapsulated enzyme in a more active conformation, and enhance the observed activity [24,25]. However, the gelatin behavior was poor with a large excess of MTMS due to the lack of the network-forming ability of TMOS.…”
Section: The Molar Ratio Of the Gel Precursorsmentioning
confidence: 99%
“…It can be best illustrated by (bio)molecular imprinting, an approach which enables the introduction of new binding sites into protein molecules (Braco et al, 1990;Dabulis and Klibanov, 1992) and the alteration of an enzyme's catalytic properties such as activity (Mingarro et al, 1995), substrate specificity (Johnsson et al, 1995;O'Rich, and Dordick, 1997) or enantioselectivity (Stahl et al, 1990(Stahl et al, , 1991. However, if ligands can be employed to alter protein conformations in organic solvents in a predictable manner, it should be possible to use this approach for the induction of ''de novo'' catalytic activity in existing proteins via imprinting with transition state analogues (TSA) (Lerner et al, 1991).…”
Section: Introductionmentioning
confidence: 99%